Cardiac Performance and Cardiopulmonary Fitness After Infection With SARS-CoV-2 - Wood, Gregory; Kirkevang, Therese Stegeager; Agergaard, Jane; Leth, Steffen; Hansen, Esben Søvsø Szocska; Laustsen, Christoffer; Larsen, Anders Hostrup; Jensen, Henrik Kjærulf; Østergaard, Lars Jørgen; Bøtker, Hans Erik; Poulsen, Steen Hvitfeldt; Kim, Won Yong (Frontiers in Cardiovascular Medicine, 2022)
Aims: Persistent cardiac symptoms are an increasingly reported phenomenon following COVID-19. However, the underlying cause of cardiac symptoms is unknown. This study aimed to identify the underlying causes, if any, of these symptoms 1 year following acute COVID-19 infection. Methods and Results: 22 individuals with persistent cardiac symptoms were prospectively investigated using echocardiography, cardiovascular magnetic resonance (CMR), 6-minute walking test, cardio-pulmonary exercise testing and electrocardiography. A median of 382 days (IQR 368, 442) passed between diagnosis of COVID-19 and investigation. As a cohort their echocardiography, CMR, 6-minute walking test and exercise testing results were within the normal ranges. There were no differences in left ventricular ejection fraction (61.460 ± 6.59 %), global longitudinal strain (19.80 ± 3.12 %) or tricuspid annular plane systolic excursion (24.96 ± 5.55 mm) as measured by echocardiography compared to a healthy control group. VO2 max (2045.00 ± 658.40 ml/min), % expected VO2 max (114.80 ± 23.08 %) and 6-minute distance walked (608.90 ± 54.51 m) exceeded that expected for the patient cohort, whilst Troponin I (5.59 ± 6.59 ng/l) and Nt-proBNP (88.18 ± 54.27 ng/l) were normal. Conclusion: Among a cohort of 22 patients with self-reported persistent cardiac symptoms, we identified no underlying cardiac disease or reduced cardiopulmonary fitness 1 year following COVID-19.